Báo cáo Tiếp thu, giải trình và chỉnh lý dự thảo Luật Phòng, chống ma túy (sửa đổi) (Số: 774/BC-UBTVQH14) - UBTVQH (2021)
Toàn văn Báo cáo Tiếp thu, giải trình và chỉnh lý dự thảo Luật Phòng, chống ma túy (sửa đổi) (Số: 774/BC-UBTVQH14)